Contested hydrosocial territories and disputed water governance: Struggles and competing claims over the Ilisu Dam development in southeastern Turkey. (May 2016) - Hommes, Lena; Boelens, Rutgerd; Maat, Harro
Highlights: Hydrosocial territories entwine physical, social, political and symbolic dimensions. Ilisu Dam's actor coalitions envision divergent hydro-social territories. The dam project is not purely about governing water but also about governing people. Actors construct techno-political discourses to (de-)justify dam materialization. Multi-actor and multi-scalar coalitions are built to strengthen counter imaginaries. Abstract: Dam development in southeastern Turkey is a highly-disputed issue, fanned by the Turkish–Kurdish conflict, socio-environmental and historical–cultural concerns, and international geopolitical interests. This paper focuses on discussions around the Ilisu Dam and shows how different actor coalitions imagine different hydrosocial territories regarding this mega-hydraulic project currently under construction. Imaginaries, counter-imaginaries and endeavours to materialize them go far beyond technical projects, portraying the dam to (re)configure the territory physically, ecologically, socio-economically, symbolically and discursively. The paper embeds competing hydro-territorial constructs and claims within an analysis of governmentality and the multi-scalar and multi-issue politics of dam opponents.